ANALISIS FAKTOR PENGHAMBAT PERTUMBUHAN PENGELOLAAN OBJEK WISATA TONGKONAN PAPA BATU - Batara, Mince; Mengga, Grace Sriati (JURNAL ILMIAH EDUNOMIKA, 2025)
Tourism development is indeed one of the focuses of national development because the tourism sector has great potential in generating foreign exchange and creating new jobs, improving the welfare of local communities, can promote the culture and local heritage of an area, and increase awareness of cultural diversity and strengthen national identity. The growth of the tourism sector in Tana Toraja Regency began to increase again, but this growth was not followed by all the attractions in Tana Toraja. And one of the objects that did not experience growth is Tongkonan Papa Batu. Even though the object is included in one of the cultural heritage in Tana TorajaRegency but the object is almost never a tourist destination that is recommended as a must-visit tourist attraction when you want to travel in Tana Toraja Therefore, the purpose of the study is to analyze the factors inhibiting the growth of the Tongkonan Papa Batu tourist attraction so that managers, government and stakeholders can use the results of this study as a reference material in developing an effective and efficient Tongkonan Papa Batu tourist attraction development strategy in the future. This research uses qualitative descriptive methods. The results obtained are that there are 6 (six) factors inhibiting the growth of management of Papa Batu Tourism Objects, namely, inadequate road access, lack of infrastructure facilities, min). Keywords : Analysis of Inhibiting Factors, Management Growth Tongkonan Papa Batu Tourist Attractio, Growth Inhibiting Factors Tourist Attraction ManagementPapa Batu's Tongkonan, Local Tourism,  Obstacles to Tourism Development, Sustainability